Plastic contamination in commercially valuable decapods caught near a major Australian urban centre - Katrina Bornt; Kathryn Linge; Simon de Lestang; Jason How; Peter Novak; Renae Hovey; Tim Langlois (Environmental Pollution, 2026)

It's not all about PFAS: Metal(loid)s are associated with physiological and metabolic changes in a native frog from conservation wetlands - Damian C. Lettoof; Rui Wang; Brad Clarke; Nicola Gray; Samuele Sala; Nick Bourne; William R. Richmond; Helen E. Nice; Peter Novak; Brenton von Takach; Bruce L. Webber; Anna H. Kaksonen; et al. (Environmental Pollution, 2025)

A single-tree approach to determine climate-growth patterns of European beech and their seasonality in the species southern distribution area - Roberto Serrano-Notivoli; Jernej Jevšenak; Edurne Martinez del Castillo; Katarina Čufar; Nina Škrk-Dolar; Giovanna Battipaglia; Jesus Julio Camarero; Andrew Hacket Pain; Alistair Jump; Renzo Motta; Paola Nola; Momchil Panayotov; et al. (Agricultural and Forest Meteorology, 2025)

Autophagic activity in the midgut cells of three arachnids responds selectively to different modes of overwintering in caves - Saška Lipovšek; Tanja Vajs; Barbara Dariš; Tone Novak; Peter Kozel (Protoplasma, 2025)

The shifting baseline of microplastic measurement: A comparison of methodologies used in estuarine-based studies and guideline recommendations - Thomas W. Crutchett; Kathryn L. Linge; Peter Novak; Julian Partridge; Harriet Paterson; Renae K. Hovey (Journal of Environmental Management, 2025)

An undocumented source of plastic contamination in sensitive estuarine environments - Katrina R. Bornt; Joshua W. Rule; Peter A. Novak (Marine Pollution Bulletin, 2025)

Body Mass–Biomass Scaling Modulates Species Keystone‐Ness to Press Perturbations - Xiaoxiao Li; Wei Yang; Mark Novak; Lei Zhao; Peter C. de Ruiter; Zhifeng Yang; Christian Guill (Ecology Letters, 2025)
Identifying species with disproportionate effects on other species under press perturbations is essential, yet how species traits and community context drive their ‘keystone‐ness’ remain unclear. We quantified keystone‐ness as linearly approximated per capita net effect derived from normalised inverse community matrices and as non‐linear per capita community biomass change from simulated perturbations in food webs with varying biomass structure. In bottom‐heavy webs (negative relationship between species' body mass and their biomass within the web), larger species at higher trophic levels tended to be keystone species, whereas in top‐heavy webs (positive body mass to biomass relationship), the opposite was true and the relationships between species' energetic traits and keystone‐ness were weakened or reversed compared to bottom‐heavy webs. Linear approximations aligned well with non‐linear responses in bottom‐heavy webs, but were less consistent in top‐heavy webs. These findings highlight the importance of community context in shaping species' keystone‐ness and informing effective conservation actions.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Incorporating high-resolution climate, remote sensing and topographic data to map annual forest growth in central and eastern Europe - Jernej Jevšenak; Marcin Klisz; Jiří Mašek; Vojtěch Čada; Pavel Janda; Miroslav Svoboda; Ondřej Vostarek; Vaclav Treml; Ernst van der Maaten; Andrei Popa; Ionel Popa; Marieke van der Maaten-Theunissen; et al. (Science of The Total Environment, 2024)

Mixing behavior of dissolved organic matter at the Yukon and Kolyma land ocean interface - Anne M. Kellerman; Peter J. Hernes; Amy M. McKenna; J. Blake Clark; Augusta Edmund; Brice Grunert; Paul J. Mann; Antonio Mannino; Michael Novak; Aron Stubbins; Maria Tzortziou; Nikita Zimov; et al. (Marine Chemistry, 2023)

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Arctic biogeochemical and optical properties of dissolved organic matter across river to sea gradients - Michael G. Novak; Antonio Mannino; J. Blake Clark; Peter Hernes; Maria Tzortziou; Robert G. M. Spencer; Anne M. Kellerman; Brice Grunert (Frontiers in Marine Science, 2022)
Arctic landscapes are warming and becoming wetter due to changes in precipitation and the timing of snowmelt which consequently alters seasonal runoff and river discharge patterns. These changes in hydrology lead to increased mobilization and transport of terrestrial dissolved organic matter (DOM) to Arctic coastal seas where significant impacts on biogeochemical cycling can occur. Here, we present measurements of dissolved organic carbon (DOC) and chromophoric DOM (CDOM) in the Yukon River-to-Bering Sea system and two river plumes on the Alaska North Slope which flow into the Beaufort Sea. Our sampling characterized optical and biogeochemical properties of DOM during high and low river discharge periods for the Yukon River-Bering Sea system. The average DOC concentration at the multiple Yukon River mouths ranged from a high of 10.36 mg C L -1 during the ascending limb of the 2019 freshet (late May), 6.4 mg C L -1 during the descending limb of the 2019 freshet (late June), and a low of 3.86 mg C L -1 during low river discharge in August 2018. CDOM absorption coefficient at 412 nm ( a CDOM (412)) averaged 8.23 m -1 , 5.07 m -1 , and 1.9 m -1 , respectively. Several approaches to model DOC concentration based on its relationship with CDOM properties demonstrated cross-system seasonal and spatial robustness for these Arctic coastal systems despite spanning an order of magnitude decrease in DOC concentration from the lower Yukon River to the Northern Bering Sea as well as the North Slope systems. “Snapshot” fluxes of DOC and CDOM across the Yukon River Delta to Norton Sound were calculated from our measurements and modeled water fluxes forced with upstream USGS river gauge data. Our findings suggest that during high river flow, DOM reaches the delta largely unaltered by inputs or physical and biogeochemical processing and that the transformations of Yukon River DOM largely occur in the plume. However, during low summer discharge, multiple processes including local precipitation events, microbial decomposition, photochemistry, and likely others can alter the DOM properties within the lower Yukon River and Delta prior to flowing into Norton Sound.

Environmental factors influencing the distribution of habitat types in the highlands of the Kamnik − Savinja Alps - Sonja Škornik; Igor Paušič; Tone Novak; Franc Janžekovič; Danijel Ivajnšič; Mihaela Tostovršnik; Peter Kozel (Plant Biosystems, 2022)

Malpighian tubules in harvestmen - Saška Lipovšek; Peter Kozel; Gerd Leitinger; Tone Novak (Protoplasma, 2021)

Planning for Change: Assessing the Potential Role of Marine Protected Areas and Fisheries Management Approaches for Resilience Management in a Changing Ocean - Kristy Kroeker; Mark Carr; Peter Raimondi; Jennifer Caselle; Libe Washburn; Stephen Palumbi; John Barth; Francis Chan; Bruce Menge; Kristen Milligan; Mark Novak; J. Wilson White (Oceanography, 2019)

Community Responses to Climate-Related Variability and Disease: The Critical Importance of Long-Term Research - Bruce Menge; Jennifer Caselle; John Barth; Carol Blanchette; Mark Carr; Francis Chan; Sarah Gravem; Tarik Gouhier; Jane Lubchenco; Margaret McManus; Kristen Milligan; Mark Novak; et al. (Oceanography, 2019)

Integrating Coastal Oceanic and Benthic Ecological Approaches for Understanding Large-Scale Meta-Ecosystem Dynamics - Bruce Menge; Jennifer Caselle; Kristen Milligan; Sarah Gravem; Tarik Gouhier; J. Wilson White; John Barth; Carol Blanchette; Mark Carr; Francis Chan; Jane Lubchenco; Margaret McManus; et al. (Oceanography, 2019)

PISCO: Advances Made Through the Formation of a Large-Scale, Long-Term Consortium for Integrated Understanding of Coastal Ecosystem Dynamics - Bruce Menge; Kristen Milligan; Jennifer Caselle; John Barth; Carol Blanchette; Mark Carr; Francis Chan; Robert Cowen; Mark Denny; Steven Gaines; Gretchen Hofmann; Kristy Kroeker; et al. (Oceanography, 2019)

How cancer cells attach to urinary bladder epithelium in vivo: study of the early stages of tumorigenesis in an orthotopic mouse bladder tumor model - Andreja Erman; Gregor Kapun; Sara Novak; Mojca Pavlin; Goran Dražić; Damjana Drobne; Peter Veranič (Histochemistry and Cell Biology, 2019)

Efficacy of remote underwater video cameras for monitoring tropical wetland fishes - Alison J. King; Amy George; Duncan J. Buckle; Peter A. Novak; Christopher J. Fulton (Hydrobiologia, 2018)

Can highland habitat type distributions replace mapping of harvestman species? - Tone Novak; Franc Janžekovič; Mihaela Rak; Danijel Ivajnšič; Peter Kozel; Ljuba Slana Novak; Sonja Škornik (Journal of Insect Conservation, 2017)

Morphological characteristics of cultured fresh and thawed pericardium cells - Olga Maslova; Oleg Fedevych; Nadiia Shuvalova; Olena Deryabina; Volodymyr Zhovnir; Miroslav Novak; Peter Kruzliak (Cell and Tissue Banking, 2016)

Temporal variation in benthic primary production in streams of the Australian wet–dry tropics - Erica A. Garcia; Neil E. Pettit; Danielle M. Warfe; Peter M. Davies; Peter M. Kyne; Peter Novak; Michael M. Douglas (Hydrobiologia, 2015)

UTP-induced ATP release is a fine-tuned signalling pathway in osteocytes - Tina M. Kringelbach; Derya Aslan; Ivana Novak; Peter Schwarz; Niklas R. Jørgensen (Purinergic Signalling, 2014)

SoilTrEC: a global initiative on critical zone research and integration - Manoj Menon; Svetla Rousseva; Nikolaos P. Nikolaidis; Pauline van Gaans; Panos Panagos; Danielle Maia de Souza; Kristin Vala Ragnarsdottir; Georg J. Lair; Liping Weng; Jaap Bloem; Pavel Kram; Martin Novak; et al. (Environmental Science and Pollution Research, 2014)

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)

Buchbesprechungen - B. M. Novak; Peter Perret (Aquatic Sciences, 1979)

Buchbesprechungen - Peter Perret; P. Bossard; B. M. Novak (Aquatic Sciences, 1974)